Respublika iqtisodiy rayonlari sanoati ixtisoslashuvining umumiy jihatlari - Roʻzmetov, D.R; Komilova, F.M (SCIENCE and SOCIETY, 2025)
The article examines the general aspects of diversification and modernization of industry in the economic regions of the republic over the years of independence and, as a consequence, changes in specialization.
Keywords: economic district; industrial specialization; diversification; modernization